Contribution of Arm Endurance, Leg Strength, and Hip Flex to Cockerical Skill Motion in Amateur Gymnastic Athletes - Ali Munir; Sumaryanti; Cerika Rismayanthi; Padli; Thesya Alda Nia; Yuni Dwi Rahmawati; Fiky Zarya (LPPM Undiksha, 2024)
The components of arm muscle endurance, leg strength, and hip flexibility are bio motor components that are indispensable in the basic kayang technique in gymnastics. These factors affect gymnastics skills in amateur gymnastics athletes. The purpose of this study was to analyze the contribution of arm endurance, leg strength, and back flexibility to kayang skills in amateur athletes at the Lampung Gymnastics Idol Club. This research method uses descriptive quantitative. The population and sample in this study were 20 athletes with a total sampling technique. Arm endurance tests using push-ups, leg strength tests using a Leg dynamometer and back flexibility tests using sit and reach, and kayang skill ability tests using kayang skill observation sheets. The data analysis technique used a multiple correlation formula and then tested with product-moment correlation analysis techniques and tested significantly. The results showed that (1) there is a significant contribution between arm endurance to kayang skills in athletes (2) there is a significant contribution between leg strength to kayang skills in athletes (3) there is a significant contribution between back flexibility to kayang skills in athletes. So it can be concluded that there is a significant contribution together between arm endurance, leg strength, and back flexibility to kayang skills in amateur athletes of Club Idola Gymnastik Lampung. So this is the importance of the coach's role in knowing the contribution of some of these components to support more optimal skill movements, especially in amateur class gymnastics athletes.